Me hijra me laxmi - Laxminarayan Tripathi; Rao, R Raj; Joshi, P G (New Delhi Oxford University Press, 2023)
He was born a boy, but never felt like one. What was he then? He felt attracted to boys. What did this make him? He loved to dance. But why did others make fun of him? Battling such emotional turmoil from a very young age, Laxminarayan Tripathi, born in a high-caste Brahman household, felt confused, trapped, and lonely. Slowly, he began wearing women's clothes. Over time, he became bold and assertive about his real sexual identity. Finally, he found his true self - she was Laxmi, a hijra. From numerous love affairs to finding solace by dancing in Mumbai's bars; from being taunted as a homo to being the first Indian hijra to attend the World AIDS Conference in Toronto; from mental and physical abuse to finding a life of grace, dignity, and fame, this autobiography is an extraordinary journey of a hijra who fought against tremendous odds for the recognition of hijras and their rights.
Keywords: English Literature